ANALYSIS OF ISLAMIC RELIGIOUS TEACHINGS FOR CHILDREN'S EDUCATION THROUGH THE ANIMATED FILM "NUSSA : THE MOVIE" - Bima Putra Anugrah; Ganjar Eka Subakti; Harry Tjahjodiningrat (Cinematology: Journal Anthology of Film and Television Studies, 2022)
Family is the first and most important education for a child before learning anything else at school. The phenomenon of children fighting their parents is a mistake in terms of educating children, educating children at this time can use audio-visual media, one of which is animated films. This study aims to provide knowledge on how to educate children contained in the animated film Nussa: The Movie. The method used is the content analysis method, using data analysis techniques by organizing data into categories, describing it into units, synthesizing, compiling it into patterns choosing which ones are important and which will be studied, verifying data, and making conclusions. The results of this study are that the animated film 'Nussa: The Movie' contains the concept of Islamic education for children including, 1) the value of teaching children to worship from an early age. 2) introduce and emulate Islamic religious figures. 3) say the sentences basmalah and hamdalah, 4). implement shared values. The implications of this research can be a reference for animators in Indonesia to continue to develop the concept of Islamic education for children in designing animated film stories.